Пылающие скалы: роман / Еремей Парнов ; послесловие А. С. Садыкова ; художник А. П. Ерасов - Парнов Еремей Иудович (Профиздат, 1984)
Экземпляры: Аб (1985) / Инвентарный номер: 8344 / Авт.знак: П 18 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6